The Importance of Packaging and Graphic Design to Communicate Corporate Social Responsibility - Natadjaja, Listia (Nirmana, 2011)
Graphic design’s function develops through time. It does not only function to inform a product but also elements to communicate Corporate Social Responsibility. As happened in catastrophic areas in Indonesia like Aceh in 2004, Nias in 2005, Jogjakarta in 2007, Bekasi District in 2009, etc. many donated products had their contributor’s information, especially the ones from corporations. There are many ways a company could implement their social responsibility. Graphic design cannot stand alone, it needs an effective media for its placement, one of them is packaging design. By using a Biskiz Susu packaging design as a case study, I try to analyze the design elements, like color, shape, brand, illustration/character, typography, and layout and then connect them with aspects like: the visual perception impact of packaging design and the importance in communicating Corporate Social Responsibility. For input information, I also discuss some consideration aspects of placing the contributor’s identity on the packaging. Based on this study, the contributor’s information in the products gives many advantages. The result shows that graphic design could be the effective element for communicating Corporate Social Responsibility and packaging design can be one of the recommended media for graphic design placement. Hopefully, this analysis could help a corporation, organization or the government in organizing the graphic design elements and considering a packaging as a medium to communicate Corporate Social Responsibility (CSR).